2022
DOI: 10.1186/s12969-022-00746-y
|View full text |Cite
|
Sign up to set email alerts
|

Standardized reporting and quantification of whole-body MRI findings in children with chronic non-bacterial osteomyelitis treated with pamidronate

Abstract: Objectives The objectives were to assess changes in radiological disease activity in children with chronic non-bacterial osteomyelitis (CNO) receiving pamidronate therapy and to test a modified radiological index for non-bacterial osteitis (mRINBO) in CNO. mRINBO was used for standardized reporting and quantification of whole-body MRI (WBMRI) findings resulting in an individual summary patient score. Methods WBMRI was retrospectively assessed in 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…The maximal index value is 10. Recently, the modified RINBO (mRINBO) index assessing CNO/CRMO patients treated with pamidronate was published by Andreasen et al, showing its clinical utility 32 .…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal index value is 10. Recently, the modified RINBO (mRINBO) index assessing CNO/CRMO patients treated with pamidronate was published by Andreasen et al, showing its clinical utility 32 .…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Thus, mRINBO might be a potential scoring method to quantify changes in radiological disease activity. However, testing of the feasibility and validity of mRIN-BO is needed 32 . Recently, Reiser et al suggested that a combination of improvement in physician global disease activity (PGDA), patient-reported overall well-being and imaging-defined disease activity measures might document the inactivity of CNO disease 43 .…”
Section: Methods For Disease Activity Evaluationmentioning
confidence: 99%
“…The data shown for bisphosphonates in Table 1[37 ▪▪ ,38 ▪ ,39,40,41 ▪ ,42 ▪ ,43 ▪ ,44,45,46,47 ▪▪ ] and TNFi in Table 2[37 ▪▪ ,38 ▪ ,39,40,41 ▪ ,42 ▪ ,43 ▪ ,44,45,47 ▪▪ ,48 ▪ ] demonstrates the difficulty of comparing retrospective outcome studies. The dosing regimens were different, and some studies used clinical outcomes measures while others reported imaging outcomes.…”
Section: Recent Reports Of Treatment Responsesmentioning
confidence: 99%
“…Standard protocols have been established and include short tau inversion recovery (STIR) or fat saturation sequences of coronal views of the whole body, the sagittal view of total spine and feet, and an axial view of the pelvis and knees [56 ▪ ,57,58 ▪ ]. Several groups have developed detailed CNO MRI scoring tools including bone marrow ‘edema’ (hyperintensity on STIR), soft tissue inflammation, hyperostosis (bony expansion), vertebral compression, and growth plate damage all showing sensitivity to change [36,47 ▪▪ ,57,59]. Further, an international group of pediatric radiologists and rheumatologists developed the CROMRIS (ChRonic nonbacterial Osteomyelitis MRI Scoring) tool through a consensus on grading CNO-specific MRI findings and on describing bone units based on anatomy [57].…”
Section: Radiologicmentioning
confidence: 99%
“…In den letzten Jahren wurden verschiedene bildgebende Instrumente (RINBO, CROMRIS) zur Unterstützung der Diagnosestellung beschrieben [53][54][55]. Hierbei wurden folgende Merkmale in der GK-MRT-Befundung herangezogen: Ausmaß der Knochenödeme und Weichteilentzündungen, Bewertung der Periostreaktion, Hyperostose, Wachstumsschädigung und Wirbelkompression [54][55][56]. Eine Validierung dieser radiologischen Diagnostiksysteme ist bisher nicht erfolgt.…”
Section: Bildgebungunclassified